Heterogeneous OH Initiated Oxidation: A Possible Explanation for the Persistence of Organophosphate Flame Retardants in Air - Liu, Yongchun; Liggio, John; Harner, Tom; Jantunen, Liisa; Shoeib, Mahiba; Li, Shao-Meng (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2014)
Heterogeneous reactions between OH radicals and emerging flame retardant compounds coated on inert particles have been investigated. Organophosphate esters (OPEs) including triphenyl phosphate (TPhP), tris-2-ethylhexyl phosphate (TEHP), and tris-1,3-dichloro-2-propyl phosphate (TDCPP) were coated on (NH4)(2)SO4 particles and exposed to OH radicals in a photochemical flow tube at 298 K and (38.0 +/- 2.0) % RH. The degradation of these particle-bound OPEs was observed as a result of OH exposure, as measured using a Time-Of-Flight Aerosol Mass Spectrometer. The derived second-order rate constants for the heterogeneous loss of TPhP, TEHP, and TDCPP were (2.1 +/- 0.19) x 10(-12) (2.7 +/- 0.63) x 10(-12), and (9.2 +/- 0.92) x 10(-13) cm(3) molecule(-1) s(-1), respectively, from which approximate atmospheric lifetimes are estimated to be 5.6 (5.2-6.0), 4.3 (3.5-5.6), and 13 (11-14) days. Additional coating of the OPE coated particles with an OH radical active species further increased the lifetimes of these OPEs. These results represent the first reported estimates of heterogeneous reaction rate constants for these species. The results demonstrate that particle bound OPEs are highly persistent in the atmosphere with regard to OH radical oxidation, consistent with the assumption that OPEs can undergo medium or long-range transport, as previously proposed on the basis of field measurements. Finally, these results indicate that future risk assessment and transport modeling of emerging priority chemicals with semi- to low-volatility must consider particle phase heterogeneous loss. processes When evaluating environmental persistence.